2013
DOI: 10.1186/1471-230x-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium leptum group bacteria abundance and diversity in the fecal microbiota of patients with inflammatory bowel disease: a case–control study in India

Abstract: BackgroundAlterations in the fecal bacterial flora occur in inflammatory bowel disease (IBD). We examined the abundance and diversity of Clostridium leptum group, an important group of carbohydrate-fermenting bacteria, in the feces of patients with IBD and compared them with healthy controls.MethodsSeventeen healthy controls (HC), 20 patients with Crohn’s disease (CD) and 22 patients with ulcerative colitis (UC) participated in the study. DNA extracted from fecal samples was amplified by PCR targeting 16S rRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
83
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 25 publications
3
83
0
3
Order By: Relevance
“…It consists of highly diverse bacterial species, many of which can produce short chain fatty acids (Miyake et al, 2015). leptum and Faecalibacterium, the most abundant members of this group, have been reported as major producers of butyrate through carbohydrate fermentation (Kabeerdoss et al, 2013;Louis and Flint, 2009). However, few species of Clostridium cluster IV have been reported to produce medium-chain carboxylic acid with the exception of Clostridium sp.…”
mentioning
confidence: 99%
“…It consists of highly diverse bacterial species, many of which can produce short chain fatty acids (Miyake et al, 2015). leptum and Faecalibacterium, the most abundant members of this group, have been reported as major producers of butyrate through carbohydrate fermentation (Kabeerdoss et al, 2013;Louis and Flint, 2009). However, few species of Clostridium cluster IV have been reported to produce medium-chain carboxylic acid with the exception of Clostridium sp.…”
mentioning
confidence: 99%
“…The reduction of total microbial diversity, increases of Enterobacteriaceae, Bacteroides-Prevotella, and decrease of Firmicutes were found in IBD patients. 38 These microbial alterations were accompanied with the immune imbalance and are believed to play a crucial role in inammatory events in IBD. In our study, using the 16S rRNA-based PCR analysis, we determined the changes of total gut bacteria and 5 specic bacteria that have been reported to be implicated in UC patients.…”
mentioning
confidence: 99%
“…The firmicute Faecalibacterium prausnitzii (Ruminococcaceae) is one of the three most abundant species, representing approximately 6 to 8% of the gut microbial community in healthy subjects, although it can reach up to 20% in some individuals (1,(4)(5)(6)(7)(8)(9)(10)(11). In contrast, depletion of F. prausnitzii has been reported to occur in several pathological disorders (for a review, see reference 12 and references therein), such as Crohn's disease (CD) (12-19), ulcerative colitis (UC) (11,14,15,17,(20)(21)(22)(23)(24)(25)(26), irritable bowel syndrome (IBS) of alternating type (27), colorectal cancer (CRC) (28, 29), and diabetes (30-32).Many studies have shown the potential role of F. prausnitzii in promoting gut health through the secretion of anti-inflammatory compounds, such as butyrate (16,(33)(34)(35)(36), and in reducing the severity of colitis induced in mice (16,37). Despite being a relatively abundant bacterium capable of regulating gut homeostasis (38, 39) and interacting in several host pathways (40), few studies have paid attention to the distribution of phylotypes within Faecalibacterium populations in the human gut.…”
mentioning
confidence: 99%
“…The firmicute Faecalibacterium prausnitzii (Ruminococcaceae) is one of the three most abundant species, representing approximately 6 to 8% of the gut microbial community in healthy subjects, although it can reach up to 20% in some individuals (1,(4)(5)(6)(7)(8)(9)(10)(11). In contrast, depletion of F. prausnitzii has been reported to occur in several pathological disorders (for a review, see reference 12 and references therein), such as Crohn's disease (CD) (12-19), ulcerative colitis (UC) (11,14,15,17,(20)(21)(22)(23)(24)(25)(26), irritable bowel syndrome (IBS) of alternating type (27), colorectal cancer (CRC) (28, 29), and diabetes (30-32).…”
mentioning
confidence: 99%